Anti-swelling high-strength and tough hydrogel with adjustable mechanical and fluorescence properties and preparation method and application thereof
The introduction of quinoline group Schiff base monomer and metal ions through solvent exchange method is carried out to construct a high-strength hydrogel that resists swelling and solves the problems of poor mechanical properties and lack of functionality in traditional hydrogels, and realizes the insulating environment The stability and fluorescence properties are associated with the detection capability of solvent environment.
Patent Information
- Application Number
- CN202210242869.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-11
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-03-11
AI Technical Summary
Traditional hydrogels have problems such as poor mechanical properties, prone to excessive swelling and lack of functionality, which are difficult to apply in underwater environments for a long time, and the fluorescence performance changes brought about by the hydrophobic association mechanism affect their solvent response.
The quinoline group Schiff base monomer and n-butyl acrylate are introduced as hydrophobic parts by solvent exchange method to form a hydrophobic association point, combined with metal ion complexing, and construct an anti-swelling high-strength hydrogel with adjustable mechanics and fluorescence properties. Achieve ionic and solvent responsiveness.
It significantly improves the mechanical properties and swelling resistance of the hydrogel, imparts its fluorescence properties to be correlated with the solvent environment, and realizes stability and detectability in the underwater environment. The tensile stress reaches 6.92MPa and the toughness is 3.52MJ. /m3, and fluorescence performance changes in different solvent environments, suitable for solvent detectors and shape memory materials.
Smart Images

Figure CN115028857B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a hydrogel, in particular to an anti-swelling high-toughness hydrogel with adjustable mechanical and fluorescence properties, a preparation method thereof, and application of the hydrogel in a solvent detector. Background Art
[0002] Hydrogel is a polymer material with a three-dimensional network structure containing water. Due to its good flexibility, designability of its constituent monomers, and the property of swelling but not dissolving in water, hydrogel has important research significance in the fields of sensors, tissue engineering, and imaging probes. However, traditional hydrogels have problems such as poor mechanical properties, easy excessive swelling, and lack of functionality, which limits the practical application of hydrogels.
[0003] Fluorescent hydrogel is a hydrogel with luminescent properties. By changing the fluorescent monomer or the excitation environment, the state of the hydrogel and the change of the intensity or wavelength of the fluorescence emission spectrum can be changed, so that the influencing factors can be visualized. Therefore, fluorescent hydrogel has been widely studied. However, fluorescent hydrogel also has the problem of weak mechanical properties. With the deepening of hydrogel application research, people have put forward higher requirements for its mechanical properties and functional properties.
[0004] There are many strategies for preparing high-strength and tough hydrogels, such as double network hydrogels, supramolecular hydrogels, nanocomposite hydrogels, topological hydrogels and hydrophobic association hydrogels. Among them, hydrophobic association hydrogels are hydrogels that use hydrophobic interactions to form physical crosslinking points to enhance toughness, which can be achieved by introducing hydrophobic monomers into hydrophilic polymers. These hydrophobic association crosslinking points, as dynamic crosslinking points, can not only increase the crosslinking density to improve the mechanical strength of the hydrogel, but also slide and unfold when subjected to external forces to dissipate energy, thereby enhancing the toughness of the hydrogel.
[0005] Hydrogels containing a large number of hydrophilic groups are usually prepared in a non-equilibrium swelling state. They will swell further in an aqueous environment, and the interaction between the polymer chains and water molecules will increase and weaken the intermolecular interaction between the polymer chains. The volume of the swollen hydrogel will expand, resulting in a significant decrease in mechanical properties, which affects the application of hydrogels in aqueous environments such as tissue engineering. According to the theory of swelling equilibrium, the method of constructing anti-swelling hydrogels is usually based on strategies such as double networks, multiple cross-linking, nanocomposites, supramolecules, multiple hydrogen bonds, and click chemistry to adjust the hydrophilicity / hydrophobicity, cross-linking density, or monomer content and components in the hydrogel. However, the constructed anti-swelling hydrogels mostly only improve the mechanical properties and stability of the hydrogel in water, lack functionality, or rarely combine functionality with anti-swelling properties.
[0006] The anti-swelling property of hydrophobic association hydrogel is relative to the water environment, so the volume of hydrophobic association anti-swelling hydrogel will change in the solvent in which the hydrophobic monomer is soluble, that is, the anti-swelling property brought by the hydrophobic association mechanism can give the hydrogel solvent responsiveness. When the hydrophobic monomer is a Schiff base hydrophobic monomer with fluorescent function, the change in the volume of the hydrogel causes the aggregation degree of the hydrophobic functional monomer to change, thereby affecting the fluorescence property of the hydrogel, that is, the solvent responsiveness of the hydrogel is associated with the fluorescence property.
[0007] However, the preparation process of introducing Schiff base hydrophobic monomers into the hydrogel system is limited by the water environment. Chinese invention patent 202010893208.6 adopts a micellar copolymerization method to wrap the Schiff base monomer containing pyridine ring acylhydrazone with Tween 80, and then polymerizes it in situ to obtain a hydrogel, successfully introducing the Schiff base hydrophobic monomer into the hydrogel system. However, in this method, the types and addition amounts of different hydrophobic monomers may be limited by the types of surfactants, and because the hydrophobic monomers are first wrapped by surfactants to form stable micelles and then polymerized, the hydrogel is easy to swell in water, cannot be used in underwater environments for a long time, and it is difficult to achieve solvent responsiveness. Summary of the invention
[0008] The purpose of the present invention is to give the hydrogel anti-swelling property and improve the mechanical properties and stability of the hydrogel in water; to provide an anti-swelling high-strength and tough hydrogel with adjustable mechanical and fluorescent properties and a preparation method thereof.
[0009] Another object of the present invention is to correlate solvent responsiveness and fluorescence properties, and to provide the application of the anti-swelling high-strength and tough hydrogel with adjustable mechanical and fluorescence properties in solvent detectors.
[0010] To achieve the above objectives, the present invention proposes the following technical solutions:
[0011] The invention discloses an anti-swelling high-strength hydrogel with adjustable mechanical and fluorescent properties, which is obtained by soaking an organic gel in deionized water for 2 to 3 days for solvent exchange and then soaking it in a metal ion solution for 6 to 12 hours; the organic gel is obtained by mixing (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide, methacrylic acid, n-butyl acrylate, and polyethylene glycol diacrylate in a third organic solvent, filling with nitrogen, adding an initiator, and polymerizing at 65 to 75°C for 4 to 10 hours; (Z)-N -(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide is prepared by dissolving (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine and triethylamine in a second organic solvent, stirring evenly, adding methacryloyl chloride dropwise, reacting under a nitrogen atmosphere, and then purifying; (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine is prepared by adding p-aminobenzoylhydrazide and quinoline-2-carboxaldehyde into a first organic solvent, adding glacial acetic acid dropwise, stirring and reacting at 80-90° C. under nitrogen protection, and then purifying.
[0012] The method for preparing the anti-swelling high-strength and tough hydrogel with adjustable mechanical and fluorescent properties comprises the following steps:
[0013] 1) adding p-aminobenzoyl hydrazide and quinoline-2-carboxaldehyde to a first organic solvent, dropping a catalyst of glacial acetic acid, and stirring the mixture at 80-90° C. for 24-48 hours under nitrogen protection; after the reaction, filtering to obtain a crude product, washing, and drying to obtain (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine;
[0014] 2) dissolving (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine and triethylamine in a second organic solvent, stirring evenly, adding methacryloyl chloride dropwise, and reacting at 50-70° C. for 12-24 hours under a nitrogen atmosphere; precipitating after the reaction, filtering to obtain a crude product, then recrystallizing and drying to obtain (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide;
[0015] 3) mixing (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide, methacrylic acid, n-butyl acrylate and polyethylene glycol diacrylate in a third organic solvent, adding an initiator after nitrogen is charged, and polymerizing at 65-75° C. for 4-10 hours to obtain an organogel;
[0016] 4) Soaking the organogel in deionized water at room temperature for 2 to 3 days for solvent exchange, changing the water every 12 to 24 hours to obtain a hydrogel;
[0017] 5) Soaking the hydrogel in a metal ion solution at room temperature for 6 to 12 hours to obtain a swelling-resistant, high-strength and tough hydrogel with adjustable mechanical and fluorescence properties.
[0018] To further achieve the purpose of the present invention, preferably, in step 1), the molar ratio of p-aminobenzoic acid hydrazide to quinoline-2-carboxaldehyde is 1:1, and the amount of glacial acetic acid added per millimole of p-aminobenzoic acid hydrazide is 0.02-0.04 ml.
[0019] Preferably, in step 2), the molar ratio of (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine to methacryloyl chloride is 1:1.1 to 1:1.6, and the molar ratio of methacryloyl chloride to triethylamine is 1:1.1 to 1:1.2.
[0020] Preferably, in step 3), the total molar concentration of methacrylic acid and n-butyl acrylate in the third organic solvent is 3 to 6 M, the molar ratio of (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide, methacrylic acid and n-butyl acrylate is 1:(50 to 114):(6 to 30), the molar concentration of polyethylene glycol diacrylate is 0.1 to 1% of the total molar concentration of methacrylic acid and n-butyl acrylate, and the amount of initiator used is 1 to 3% of the total mass of methacrylic acid and n-butyl acrylate.
[0021] Preferably, the relative molecular mass of the polyethylene glycol diacrylate is one or more of 400, 600 and 1000; and the initiator is azobisisobutyronitrile, potassium persulfate or ammonium persulfate.
[0022] Preferably, in step 1), the first organic solvent is one or more of acetonitrile, methanol and dimethyl sulfoxide; in step 2), the second organic solvent is N-methylpyrrolidone; in step 3), the third organic solvent is one or more of acetone and dimethyl sulfoxide.
[0023] Preferably, in step 1), the washing is performed with isopropanol; in step 2), the precipitation is performed in water, and the recrystallization is performed by dissolving the crude product in pyridine and then recrystallizing it in n-hexane or ether; in step 4), each gram of the organogel is soaked in 100-200 ml of deionized water.
[0024] Preferably, in step 5), the metal ion solution includes Zn 2+ , Cu 2+ 、Al 3+ , Ga 2+ or Fe 3+ The solution is prepared by dissolving zinc acetate dihydrate, anhydrous copper acetate, aluminum nitrate nonahydrate, anhydrous calcium chloride or ferric chloride hexahydrate in deionized water; 4 to 8 ml of 0.001 to 0.3 M metal ion solution is added to each gram of hydrogel.
[0025] The application of the anti-swelling high-toughness hydrogel with adjustable mechanical and fluorescent properties in solvent detectors. Its fluorescence properties are adjustable, and its intensity and color will respond to changes in mixed solvents with different proportions that are good or bad solvents relative to hydrophobic monomers. In mixed solvents of dimethyl sulfoxide and water with different proportions, the maximum emission peak position of the Schiff base metal complex hydrogel shifts from 485nm to 503nm, and the color gradually changes from blue to green, which can be used for detection of solvent leakage in water. The anti-swelling high-toughness hydrogel with adjustable mechanical and fluorescent properties has application potential in the fields of shape memory materials, optical flexible devices, underwater sensors, etc.
[0026] The anti-swelling high-toughness hydrogel with adjustable mechanical and fluorescent properties of the present invention is a metal complex hydrogel, referred to as metal complex hydrogel in the application document.
[0027] The present invention synthesizes a Schiff base monomer containing a quinoline group, and introduces it and n-butyl acrylate as a hydrophobic part into a hydrogel system with methacrylic acid as a hydrophilic monomer through a solvent exchange method. The hydrophilic and hydrophobic monomers are uniformly distributed and polymerized in the organic gel, and after solvent exchange in an aqueous environment, the hydrophobic monomers spontaneously undergo hydrophobic association to form hydrophobic association points, which increases the crosslinking density and thus enhances the mechanical strength. At the same time, the reversible hydrophobic association points can serve as an energy dissipation mechanism in the hydrogel when subjected to stress, thereby improving its ductility. In addition, the introduction of the Schiff base monomer containing a quinoline group also gives the hydrogel fluorescent properties and ion responsiveness, and exhibits obvious changes in fluorescent properties when complexed with metal ions. At the same time, the carboxyl group of methacrylic acid is also complexed with metal ions, and the metal coordination bonds formed by the two can also enhance the mechanical properties of the hydrogel and have adjustability.
[0028] The adjustability of the mechanical and fluorescent properties of the hydrogel of the present invention comes from the ion and solvent responsiveness brought about by the ion complexation and hydrophobic association mechanisms. These two different response mechanisms give the hydrogel two independent shape memory mechanisms, making it more flexible in the application of shape memory materials. At the same time, the complexation and detachment of metal ions make the hydrogel also accompanied by changes in fluorescence during the shape change process.
[0029] The preparation method and the prepared hydrogel of the present invention have the following advantages and beneficial effects:
[0030] 1) The gelling method of the present invention is flexible in design and can be adjusted according to different mechanical property requirements by changing the ratio of hydrophilic and hydrophobic monomers and the concentration of metal ions in the hydrogel; the gelling method is simple and theoretically applicable to other hydrophobic functional monomers, and the type and addition amount of the hydrophobic monomer are not limited.
[0031] 2) The fluorescence change of the Schiff base monomer containing quinoline group synthesized by the present invention before and after complexing with metal ions is obvious and can be discerned by naked eyes, and has good recognition ability. In addition to changing with ion complexation, its fluorescence performance can also respond to changes in the solvent environment, making the solvent environment in which the hydrogel is located visualized and detectable.
[0032] 3) The high-strength and tough hydrogel prepared by the present invention has excellent mechanical properties and anti-swelling properties, with a maximum tensile stress of 6.92MPa and a maximum toughness of 3.52MJ / m 3 After complexing with metal ions, the maximum tensile stress can reach 11.24MPa. The hydrogel is completely immersed in water for 8 days, and the equilibrium water content is 56.7±1%, which has good anti-swelling properties.
[0033] 4) The present invention combines the anti-swelling property with the fluorescent function to construct an anti-swelling hydrogel with fluorescent function, which enhances its stability in the water environment while giving the hydrogel specific functions, and associates the changes in the two properties, thereby promoting the practical application of the hydrogel in the fields of tissue engineering, medical sealants and underwater sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic diagram of the hydrophobic association and ion complex structure of the present invention.
[0035] Figure 2 The (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine obtained in Example 1 was reacted with d6-DMSO as solvent. 1 HNMR spectrum.
[0036] Figure 3 The (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide obtained in Example 1 was reacted with d6-DMSO as solvent. 1 H NMR spectrum.
[0037] Figure 4 This is a graph showing the change in equilibrium moisture content of the hydrogel obtained in Example 1 at different immersion times.
[0038] Figure 5 The stress-strain curves of the hydrogels obtained in Example 1, Example 2, and Example 3 are shown.
[0039] Figure 6 The stress-strain curves of the metal complex hydrogels obtained in Example 1, Example 4, Example 5, and Example 6 are shown.
[0040] Figure 7 The fluorescence emission spectra of the hydrogel obtained in Example 1 before and after metal ion complexation.
[0041] Figure 8 The fluorescence emission spectra and physical images of the metal ion complex hydrogel obtained in Example 1 in solvents with different mixing ratios.
[0042] Fig. 9 This is a diagram showing the shape memory effect of the hydrogel obtained in Example 1. DETAILED DESCRIPTION
[0043] In order to better understand the present invention, the present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0044] In the following examples, unless otherwise specified, the properties of the hydrogels were tested using the following methods:
[0045] (1) Anti-swelling performance test: Place a hydrogel sample with a diameter of 20 mm and a thickness of 1 mm in a 70°C oven and dry it to constant weight, and weigh the dry gel weight m0. Then, immerse the dry gel completely in deionized water at room temperature, take it out at regular intervals (0.25, 0.5, 0.75, 1, 6, 12, 24 h), absorb the excess water on the surface with filter paper, and weigh it to obtain the weight of the hydrogel after water absorption m t The swelling equilibrium of the hydrogel after immersion for t time is described by the water content F:
[0046]
[0047] (2) Tensile property test: A rectangular hydrogel sample was tested on a KJ-1065A-T tensile strength testing machine at room temperature. The actual measured length of the sample was 10 mm, the thickness was 1 mm, the width was 4 mm, and the tensile rate was 100 mm / min.
[0048] (3) Fluorescence performance test: The fluorescence test of the hydrogel was carried out in a Hitachi F-4500 fluorescence spectrophotometer. The size of the tested hydrogel sample was 15 mm × 7.5 mm × 1 mm, and it was placed between two glass slides for fixed testing. The excitation wavelength was 377 nm, and the excitation and emission slits were 10 nm.
[0049] (4) Performance of solvent detection: The same hydrogel samples were placed in 2 ml of a mixed solvent of water and dimethyl sulfoxide in different ratios for 2 minutes. The ratios were 10:0, 7:3, 5:5, 3:7, and 0:10, respectively, and then the fluorescence performance was tested.
[0050] (5) Shape memory performance: The organogel with the size of 50 mm × 7.5 mm × 1 mm was placed in water for 5 minutes to fix the shape of the left end. 2+The right end of the probe was placed in an aqueous solution for 30 seconds to fix its shape, then immersed in an ethylenediaminetetraacetic acid (EDTA) solution for 30 minutes to restore its right end to its original shape, and finally placed in dimethyl sulfoxide (DMSO) for 2 minutes to restore its left end to its original shape. At each stage, the fluorescence changes were observed under natural light and 365nm ultraviolet light.
[0051] The present invention utilizes micellar copolymerization to prepare a hydrogel containing a Schiff base monomer. The types and addition amounts of different hydrophobic monomers introduced may be limited by the types of surfactants, and the hydrogel is prone to swelling in water, and cannot be used in underwater environments for a long time. The present invention introduces a quinoline group-containing Schiff base hydrophobic monomer with fluorescent properties as part of the hydrophobic structure into the hydrogel through a solvent exchange method to construct an anti-swelling hydrogel, thereby giving the hydrogel anti-swelling properties so that it can be used in underwater environments, and the solvent responsiveness brought about by the anti-swelling is associated with the fluorescent properties to achieve visualization and detectability of the solvent environment in which the hydrogel is located. In addition, the Schiff base monomer introduced into the hydrogel is not limited by the surfactant, and the mechanical and fluorescent properties of the hydrogel are adjustable. Figure 1 In a, after the Schiff base monomer containing quinoline group and n-butyl acrylate are introduced into the polymer network, hydrophobic association points are formed in the hydrogel due to the hydrophobic effect after solvent exchange. It can be seen from Examples 1-4 that the tensile stress of the control hydrogel without hydrophobic part is 0.031MPa and the tensile strain is 20%, while the tensile stress of the hydrogel containing hydrophobic part is 1.70-6.92MPa and the tensile strain is 21-368%. Therefore, the hydrophobic association mechanism significantly improves its mechanical properties. Figure 1 b, after the hydrogel prepared by the present invention is immersed in a metal ion solution, the carboxyl groups and quinoline Schiff base groups in the polymer network react with Zn 2+ The complexation forms a metal coordination bond, which produces bright blue light under ultraviolet light, giving the hydrogel ion responsiveness and changing the mechanical and fluorescence properties of the hydrogel.
[0052] Example 1
[0053] A method for preparing a swelling-resistant and high-strength hydrogel with adjustable mechanical and fluorescent properties comprises the following steps:
[0054] (1) Preparation of (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine: 7 mmol of p-aminobenzoyl hydrazide and 7 mmol of quinoline-2-carboxaldehyde were added to acetonitrile, and 0.14 ml of glacial acetic acid was added dropwise as a catalyst. The mixture was stirred at 85°C for 24 h under nitrogen protection. After the reaction, the crude product was filtered to obtain the product, which was washed with isopropanol, filtered, and dried. Preparation of (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine with d6-DMSO as solvent 1 H NMR spectrum Figure 2 shown.
[0055] (2) Preparation of (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide: 2mmol (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine and 3.4mmol triethylamine were dissolved in N-methylpyrrolidone, stirred evenly, and then 3mmol methacryloyl chloride was added dropwise. The mixture was reacted at 60°C for 12h under nitrogen atmosphere. After the reaction, the mixture was precipitated in water and filtered to obtain a crude product. The crude product was dissolved in pyridine, recrystallized in n-hexane, and dried. Preparation of (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide using d6-DMSO as solvent 1 H NMR spectrum Figure 3 shown.
[0056] (3) Preparation of organogel: 0.05 mmol (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide, 5.7 mmol methacrylic acid, 0.3 mmol n-butyl acrylate, and 0.006 mmol polyethylene glycol diacrylate (relative molecular weight 400) were mixed evenly in 1 ml of dimethyl sulfoxide, filled with nitrogen, and 5.8 mg of azobisisobutyronitrile was added. The mixture was polymerized at 65°C for 4 h to obtain an organogel.
[0057] (4) Preparation of hydrogel: The organogel was immersed in 200 ml of deionized water at room temperature for 2 days for solvent exchange, and the water was changed every 12 hours to obtain a hydrogel.
[0058] (5) Preparation of metal complex hydrogel: The hydrogel was immersed in 6 ml of 0.00625 M Zn 2+ After 9 hours in the solution, a metal complex hydrogel was obtained.
[0059] Depend on Figure 4 It can be seen that in the anti-swelling performance test experiment, the water content of the hydrogel prepared in this embodiment reached 56.1% when immersed in water for 13 hours. This is because a large number of hydrophilic groups in the polymer chain attract water molecules into the hydrogel. Subsequently, the hydrophobic groups in the hydrogel undergo hydrophobic association due to the hydrophobic effect, which limits the further swelling of the hydrogel. The hydrogel that reaches swelling equilibrium continues to be immersed in water, and the equilibrium water content remains at 56.7±1% within 8 days. Therefore, the hydrogel can be stored in water without worrying about its swelling problem, and has the potential to be used as an underwater material.
[0060] Depend on Figure 5 It can be seen that the tensile stress of the hydrogel is 1.70MPa, the tensile strain is 368%, and the toughness is 3.52MJ / m 3The tensile stress of the polymethacrylic acid hydrogel prepared by the same method but without the addition of hydrophobic monomers is 0.031 MPa and the tensile strain is 20%. Compared with the two, it can be seen that the hydrophobic association significantly enhances the mechanical properties of the hydrogel. This is because the hydrophobic association points increase the cross-linking density and can serve as an energy dissipation mechanism in the hydrogel when subjected to stress, thereby improving its ductility. And combined with Figure 5 From the stress-strain curves of the hydrogels in Examples 2 and 3, it can be seen that when the molar concentration ratio of the hydrophilic and hydrophobic monomers is changed, the mechanical properties of the hydrogel will also change significantly. Therefore, the mechanical properties can be adjusted by changing the ratio of the hydrophilic and hydrophobic monomers to meet the specific requirements of the material.
[0061] The hydrogels were immersed in solutions with different metal ion concentrations to obtain metal complex hydrogels with different mechanical properties, such as Figure 6 When the metal ion concentration is 0.00625M, the tensile stress is 1.75MPa and the tensile strain is 310%. As the metal ion concentration increases, the tensile stress of the metal complex hydrogel gradually increases, while the tensile strain gradually decreases. When the metal ion concentration is 0.3M, the tensile stress is 11.24MPa and the tensile strain is 8.7%. Therefore, the mechanical properties can also be adjusted by changing the metal ion concentration to meet the specific needs of the material.
[0062] Depend on Figure 7 It can be seen that the hydrogel exhibits bright blue light after metal ion complexation, with a maximum emission peak of 485nm. The fluorescence intensity changes significantly before and after ion complexation, and has potential for application in ion recognition sensors. Figure 8 It can be seen that the fluorescence emission spectra of the metal complex hydrogel after being immersed in mixed solvents with different ratios of water and dimethyl sulfoxide change. Since the dimethyl sulfoxide solvent is a good solvent for hydrophobic quinoline groups and n-butyl ester groups, the hydrophobic effect is weakened, and the spatial position of the group is released. As the proportion of dimethyl sulfoxide increases, the fluorescence intensity gradually decreases, the maximum emission peak position shifts from 485nm to 503nm, and the color gradually changes from blue to green. Therefore, it can be used as a solvent detector to monitor whether a solvent that is a good solvent for hydrophobic monomers has leaked in the water, and the anti-swelling property allows the hydrogel to be stored and work in an aqueous environment for a long time, while having good mechanical properties.
[0063] In addition, based on the above hydrogel properties, it can be used in shape memory materials. Fig. 9It can be seen that through the treatment of water, metal ion solution, ethylenediaminetetraacetic acid, and dimethyl sulfoxide, the hydrogel exhibits a cyclic dual shape memory performance. The left end of the hydrogel was placed in water for 5 minutes and fixed at 90° due to hydrophobic association; the right end of the hydrogel was ion complexed for 30 seconds and was also fixed at 90°; it was immersed in ethylenediaminetetraacetic acid for 30 minutes and restored its shape due to the weakening of ion complexation; it was immersed in dimethyl sulfoxide for 2 minutes and restored its shape due to the weakening of hydrophobic association. At the same time, the fluorescence of the hydrogel under ultraviolet light was enhanced after metal ion complexation, and the fluorescence of the hydrogel was weakened after immersion in ethylenediaminetetraacetic acid.
[0064] Example 2
[0065] A method for preparing a swelling-resistant and high-strength hydrogel with adjustable mechanical and fluorescent properties comprises the following steps:
[0066] (1) Preparation of (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine: 7 mmol of p-aminobenzoyl hydrazide and 7 mmol of quinoline-2-carboxaldehyde were added to acetonitrile, and 0.14 ml of glacial acetic acid was added dropwise as a catalyst. The mixture was stirred at 85°C for 24 h under nitrogen protection. After the reaction was completed, the crude product was filtered to obtain the crude product, which was washed in isopropanol, filtered, and dried.
[0067] (2) Preparation of (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide: 2 mmol (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine and 3.4 mmol triethylamine were dissolved in N-methylpyrrolidone, stirred evenly, and then 3 mmol methacryloyl chloride was added dropwise. The mixture was reacted at 60°C for 12 h under a nitrogen atmosphere. After the reaction was completed, the mixture was precipitated in water and filtered to obtain a crude product. The crude product was dissolved in pyridine, recrystallized in n-hexane, and dried.
[0068] (3) Preparation of organogel: 0.05 mmol (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide, 5.1 mmol methacrylic acid, 0.9 mmol n-butyl acrylate, and 0.006 mmol polyethylene glycol diacrylate (relative molecular weight 400) were mixed evenly in 1 ml of dimethyl sulfoxide, filled with nitrogen, and 5.8 mg azobisisobutyronitrile was added. The mixture was polymerized at 65°C for 4 h to obtain an organogel.
[0069] (4) Preparation of hydrogel: The organogel was immersed in 200 ml of deionized water at room temperature for 2 days for solvent exchange, and the water was changed every 18 hours to obtain a hydrogel.
[0070] (5) Preparation of metal complex hydrogel: The hydrogel was immersed in 6 ml of 0.1 M Zn 2+ After 9 hours in the solution, a metal complex hydrogel was obtained.
[0071] Depend on Figure 5 It can be seen that the tensile stress of the hydrogel in Example 2 is 6.92MPa, the tensile strain is 61%, and the toughness is 3.26MJ / m 3 . In addition, the metal complex hydrogel was immersed in a mixed solvent with different ratios of water and dimethyl sulfoxide. As the proportion of dimethyl sulfoxide increased, its fluorescence intensity gradually decreased, the maximum emission peak position shifted from 485nm to 503nm, and the color gradually changed from blue to green. The hydrogel exhibited a recyclable dual shape memory property. The left end of the hydrogel was placed in water for 5 minutes and fixed at 90° due to hydrophobic association; the right end of the hydrogel was ion-complexed for 30 seconds and was also fixed at 90°; it was immersed in dimethyl sulfoxide for 2 minutes and restored its shape due to the weakening of hydrophobic association; it was immersed in ethylenediaminetetraacetic acid for 30 minutes and restored its shape due to the weakening of ion complexation. At the same time, the fluorescence of the hydrogel under ultraviolet light was enhanced after metal ion complexation, and the fluorescence of the hydrogel was weakened after being immersed in ethylenediaminetetraacetic acid.
[0072] Example 3
[0073] A method for preparing a swelling-resistant and high-strength hydrogel with adjustable mechanical and fluorescent properties comprises the following steps:
[0074] (1) Preparation of (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine: 7 mmol of p-aminobenzoyl hydrazide and 7 mmol of quinoline-2-carboxaldehyde were added to acetonitrile, and 0.14 ml of glacial acetic acid was added dropwise as a catalyst. The mixture was stirred at 85°C for 24 h under nitrogen protection. After the reaction was completed, the crude product was filtered to obtain the crude product, which was washed in isopropanol, filtered, and dried.
[0075] (2) Preparation of (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide: 2 mmol (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine and 3.4 mmol triethylamine were dissolved in N-methylpyrrolidone, stirred evenly, and then 3 mmol methacryloyl chloride was added dropwise. The mixture was reacted at 60°C for 12 h under a nitrogen atmosphere. After the reaction was completed, the mixture was precipitated in water and filtered to obtain a crude product. The crude product was dissolved in pyridine, recrystallized in n-hexane, and dried.
[0076] (3) Preparation of organogel: 0.05 mmol (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide, 4.5 mmol methacrylic acid, 1.5 mmol n-butyl acrylate, and 0.006 mmol polyethylene glycol diacrylate (relative molecular weight 400) were mixed evenly in 1 ml of dimethyl sulfoxide, filled with nitrogen, and 5.8 mg of azobisisobutyronitrile was added. The mixture was polymerized at 65°C for 4 h to obtain an organogel.
[0077] (4) Preparation of hydrogel: The organogel was immersed in 200 ml of deionized water at room temperature for 3 days for solvent exchange, and the water was changed every 12 hours to obtain a hydrogel.
[0078] (5) Preparation of metal complex hydrogel: The hydrogel was immersed in 6 ml of 0.1 M Zn 2+ After 9 hours in the solution, a metal complex hydrogel was obtained.
[0079] Depend on Figure 5 It can be seen that the tensile stress of the hydrogel in Example 3 is 5.37 MPa, the tensile strain is 21%, and the toughness is 0.91 MJ / m 3 . In addition, the metal complex hydrogel was immersed in a mixed solvent with different ratios of water and dimethyl sulfoxide. As the proportion of dimethyl sulfoxide increased, its fluorescence intensity gradually decreased, the maximum emission peak position shifted from 485nm to 503nm, and the color gradually changed from blue to green. The hydrogel exhibited a recyclable dual shape memory property. The left end of the hydrogel was placed in water for 5 minutes and fixed at 90° due to hydrophobic association; the right end of the hydrogel was ion-complexed for 30 seconds and was also fixed at 90°; it was immersed in dimethyl sulfoxide for 2 minutes and restored its shape due to the weakening of hydrophobic association; it was immersed in ethylenediaminetetraacetic acid for 30 minutes and restored its shape due to the weakening of ion complexation. At the same time, the fluorescence of the hydrogel under ultraviolet light was enhanced after metal ion complexation, and the fluorescence of the hydrogel was weakened after being immersed in ethylenediaminetetraacetic acid.
[0080] Example 4
[0081] A method for preparing a swelling-resistant and high-strength hydrogel with adjustable mechanical and fluorescent properties comprises the following steps:
[0082] (1) Preparation of (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine: 7 mmol of p-aminobenzoyl hydrazide and 7 mmol of quinoline-2-carboxaldehyde were added to acetonitrile, and 0.14 ml of glacial acetic acid was added dropwise as a catalyst. The mixture was stirred at 85°C for 24 h under nitrogen protection. After the reaction was completed, the crude product was filtered to obtain the crude product, which was washed in isopropanol, filtered, and dried.
[0083] (2) Preparation of (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide: 2 mmol (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine and 3.4 mmol triethylamine were dissolved in N-methylpyrrolidone, stirred evenly, and then 3 mmol methacryloyl chloride was added dropwise. The mixture was reacted at 60°C for 12 h under a nitrogen atmosphere. After the reaction was completed, the mixture was precipitated in water and filtered to obtain a crude product. The crude product was dissolved in pyridine, recrystallized in n-hexane, and dried.
[0084] (3) Preparation of organogel: 0.05 mmol (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide, 5.7 mmol methacrylic acid, 0.3 mmol n-butyl acrylate, and 0.006 mmol polyethylene glycol diacrylate (relative molecular weight 400) were mixed evenly in 1 ml of dimethyl sulfoxide, filled with nitrogen, and 5.8 mg of azobisisobutyronitrile was added. The mixture was polymerized at 65°C for 4 h to obtain an organogel.
[0085] (4) Preparation of hydrogel: The organogel was immersed in 200 ml of deionized water at room temperature for 3 days for solvent exchange, and the water was changed every 18 hours to obtain a hydrogel.
[0086] (5) Preparation of metal complex hydrogel: The hydrogel was immersed in 6 ml of 0.025 M Zn 2+ After 9 hours in the solution, a metal complex hydrogel was obtained.
[0087] The tensile stress of the metal complex hydrogel in this embodiment is 1.8 MPa, the tensile strain is 168%, and the toughness is 1.77 MJ / m 3 . In addition, the metal complex hydrogel was immersed in a mixed solvent with different ratios of water and dimethyl sulfoxide. As the proportion of dimethyl sulfoxide increased, its fluorescence intensity gradually decreased, the maximum emission peak position shifted from 485nm to 503nm, and the color gradually changed from blue to green. The hydrogel exhibited a recyclable dual shape memory property. The left end of the hydrogel was placed in water for 5 minutes and fixed at 90° due to hydrophobic association; the right end of the hydrogel was ion-complexed for 30 seconds and was also fixed at 90°; it was immersed in dimethyl sulfoxide for 2 minutes and restored its shape due to the weakening of hydrophobic association; it was immersed in ethylenediaminetetraacetic acid for 30 minutes and restored its shape due to the weakening of ion complexation. At the same time, the fluorescence of the hydrogel under ultraviolet light was enhanced after metal ion complexation, and the fluorescence of the hydrogel was weakened after being immersed in ethylenediaminetetraacetic acid.
[0088] Example 5
[0089] A method for preparing a swelling-resistant and high-strength hydrogel with adjustable mechanical and fluorescent properties comprises the following steps:
[0090] (1) Preparation of (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine: 7 mmol of p-aminobenzoyl hydrazide and 7 mmol of quinoline-2-carboxaldehyde were added to acetonitrile, and 0.14 ml of glacial acetic acid was added dropwise as a catalyst. The mixture was stirred at 85°C for 24 h under nitrogen protection. After the reaction was completed, the crude product was filtered to obtain the crude product, which was washed in isopropanol, filtered, and dried.
[0091] (2) Preparation of (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide: 2 mmol (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine and 3.4 mmol triethylamine were dissolved in N-methylpyrrolidone, stirred evenly, and then 3 mmol methacryloyl chloride was added dropwise. The mixture was reacted at 60°C for 12 h under a nitrogen atmosphere. After the reaction was completed, the mixture was precipitated in water and filtered to obtain a crude product. The crude product was dissolved in pyridine, recrystallized in n-hexane, and dried.
[0092] (3) Preparation of organogel: 0.05 mmol (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide, 5.7 mmol methacrylic acid, 0.3 mmol n-butyl acrylate, and 0.006 mmol polyethylene glycol diacrylate (relative molecular weight 400) were mixed evenly in 1 ml of dimethyl sulfoxide, filled with nitrogen, and 5.8 mg of azobisisobutyronitrile was added. The mixture was polymerized at 65°C for 4 h to obtain an organogel.
[0093] (4) Preparation of hydrogel: The organogel was immersed in 200 ml of deionized water at room temperature for 3 days for solvent exchange, and the water was changed every 18 hours to obtain a hydrogel.
[0094] (5) Preparation of metal complex hydrogel: The hydrogel was immersed in 6 ml of 0.1 M Zn 2+ After 9 hours in the solution, a metal complex hydrogel was obtained.
[0095] The tensile stress of the metal complex hydrogel in this embodiment is 5.97 MPa, the tensile strain is 10%, and the toughness is 0.72 MJ / m 3 . In addition, the metal complex hydrogel was immersed in a mixed solvent with different ratios of water and dimethyl sulfoxide. As the proportion of dimethyl sulfoxide increased, its fluorescence intensity gradually decreased, the maximum emission peak position shifted from 485nm to 503nm, and the color gradually changed from blue to green. The hydrogel exhibited a recyclable dual shape memory property. The left end of the hydrogel was placed in water for 5 minutes and fixed at 90° due to hydrophobic association; the right end of the hydrogel was ion-complexed for 30 seconds and was also fixed at 90°; it was immersed in dimethyl sulfoxide for 2 minutes and restored its shape due to the weakening of hydrophobic association; it was immersed in ethylenediaminetetraacetic acid for 30 minutes and restored its shape due to the weakening of ion complexation. At the same time, the fluorescence of the hydrogel under ultraviolet light was enhanced after metal ion complexation, and the fluorescence of the hydrogel was weakened after being immersed in ethylenediaminetetraacetic acid.
[0096] Example 6
[0097] A method for preparing a swelling-resistant and high-strength hydrogel with adjustable mechanical and fluorescent properties comprises the following steps:
[0098] (1) Preparation of (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine: 7 mmol of p-aminobenzoyl hydrazide and 7 mmol of quinoline-2-carboxaldehyde were added to acetonitrile, and 0.14 ml of glacial acetic acid was added dropwise as a catalyst. The mixture was stirred at 85°C for 24 h under nitrogen protection. After the reaction was completed, the crude product was filtered to obtain the crude product, which was washed in isopropanol, filtered, and dried.
[0099] (2) Preparation of (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide: 2 mmol (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine and 3.4 mmol triethylamine were dissolved in N-methylpyrrolidone, stirred evenly, and then 3 mmol methacryloyl chloride was added dropwise. The mixture was reacted at 60°C for 12 h under a nitrogen atmosphere. After the reaction was completed, the mixture was precipitated in water and filtered to obtain a crude product. The crude product was dissolved in pyridine, recrystallized in n-hexane, and dried.
[0100] (3) Preparation of organogel: 0.05 mmol (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide, 5.7 mmol methacrylic acid, 0.3 mmol n-butyl acrylate, and 0.006 mmol polyethylene glycol diacrylate (relative molecular weight 400) were mixed evenly in 1 ml of dimethyl sulfoxide, filled with nitrogen, and 5.8 mg of azobisisobutyronitrile was added. The mixture was polymerized at 65°C for 4 h to obtain an organogel.
[0101] (4) Preparation of hydrogel: The organogel was immersed in 200 ml of deionized water at room temperature for 3 days for solvent exchange, and the water was changed every 24 hours to obtain a hydrogel.
[0102] (5) Preparation of metal complex hydrogel: The hydrogel was immersed in 6 ml of 0.3 M Zn 2+ After 9 hours in the solution, a metal complex hydrogel was obtained.
[0103] The tensile stress of the metal complex hydrogel in this embodiment is 11.24 MPa, the tensile strain is 8.7%, and the toughness is 0.61 MJ / m 3. In addition, the metal complex hydrogel was immersed in a mixed solvent with different ratios of water and dimethyl sulfoxide. As the proportion of dimethyl sulfoxide increased, its fluorescence intensity gradually decreased, the maximum emission peak position shifted from 485nm to 503nm, and the color gradually changed from blue to green. The hydrogel exhibited a recyclable dual shape memory property. The left end of the hydrogel was placed in water for 5 minutes and fixed at 90° due to hydrophobic association; the right end of the hydrogel was ion-complexed for 30 seconds and was also fixed at 90°; it was immersed in dimethyl sulfoxide for 2 minutes and restored its shape due to the weakening of hydrophobic association; it was immersed in ethylenediaminetetraacetic acid for 30 minutes and restored its shape due to the weakening of ion complexation. At the same time, the fluorescence of the hydrogel under ultraviolet light was enhanced after metal ion complexation, and the fluorescence of the hydrogel was weakened after being immersed in ethylenediaminetetraacetic acid.
[0104] Example 7
[0105] A method for preparing a swelling-resistant and high-strength hydrogel with adjustable mechanical and fluorescent properties comprises the following steps:
[0106] (1) Preparation of (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine: 7 mmol of p-aminobenzoyl hydrazide and 7 mmol of quinoline-2-carboxaldehyde were added to acetonitrile, and 0.14 ml of glacial acetic acid was added dropwise as a catalyst. The mixture was stirred at 80°C for 48 h under nitrogen protection. After the reaction was completed, the crude product was filtered to obtain the crude product, which was washed in isopropanol, filtered, and dried.
[0107] (2) Preparation of (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide: 2 mmol (Z)-4-amino-N'-(quinoline-2-methylene)phenylhydrazine and 3.2 mmol triethylamine were dissolved in N-methylpyrrolidone, stirred evenly, and then 2.8 mmol methacryloyl chloride was added dropwise. The mixture was reacted at 50°C for 24 h under a nitrogen atmosphere. After the reaction was completed, the mixture was precipitated in water and filtered to obtain a crude product. The crude product was dissolved in pyridine, recrystallized in ether, and dried.
[0108] (3) Preparation of organogel: 0.08 mmol (Z)-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide, 4.5 mmol methacrylic acid, 1.5 mmol n-butyl acrylate, and 0.006 mmol polyethylene glycol diacrylate (relative molecular weight 400) were mixed evenly in 1 ml of dimethyl sulfoxide, filled with nitrogen, and then 5.8 mg potassium persulfate was added. The mixture was polymerized at 70°C for 6 h to obtain an organogel.
[0109] (4) Preparation of hydrogel: The organogel was immersed in 200 ml of deionized water at room temperature for 3 days for solvent exchange, and the water was changed every 24 hours to obtain a hydrogel.
[0110] (5) Preparation of metal complex hydrogel: The hydrogel was immersed in 6 ml of 0.1 M Zn 2+ After 9 hours in the solution, a metal complex hydrogel was obtained.
[0111] The tensile stress of the hydrogel in this embodiment is 5.9 MPa, the tensile strain is 37%, and the toughness is 0.90 MJ / m 3 . In addition, the metal complex hydrogel was immersed in a mixed solvent with different ratios of water and dimethyl sulfoxide. As the proportion of dimethyl sulfoxide increased, its fluorescence intensity gradually decreased, the maximum emission peak position shifted from 485nm to 503nm, and the color gradually changed from blue to green. The hydrogel exhibited a recyclable dual shape memory property. The left end of the hydrogel was placed in water for 5 minutes and fixed at 90° due to hydrophobic association; the right end of the hydrogel was ion-complexed for 30 seconds and was also fixed at 90°; it was immersed in dimethyl sulfoxide for 2 minutes and restored its shape due to the weakening of hydrophobic association; it was immersed in ethylenediaminetetraacetic acid for 30 minutes and restored its shape due to the weakening of ion complexation. At the same time, the fluorescence of the hydrogel under ultraviolet light was enhanced after metal ion complexation, and the fluorescence of the hydrogel was weakened after being immersed in ethylenediaminetetraacetic acid.
[0112] Compared with Chinese invention patent 202010893208.6, the amount of Schiff base monomer containing quinoline group in the hydrogel prepared by the solvent exchange method of the present invention is not limited by surfactants, and has a larger mechanical property adjustment range and anti-swelling performance. Under the influence of the hydrophilic and hydrophobic monomer ratio, the hydrogel of the present invention has a tensile stress of 1.70-6.92MPa, a tensile strain of 21-368%, and a toughness of 0.90-3.52MJ / m 3 ; Under the influence of the concentration of metal ion solution, the tensile stress is increased to 1.75-11.24MPa, and the tensile strain is 8.7-310%; the hydrogel is completely immersed in water for 8 days and the equilibrium water content is 56.7±1%, which has good anti-swelling properties. And on the basis of the anti-swelling properties given by ion complexation and hydrophobic association mechanisms, its fluorescence properties can respond to changes in the solvent environment in addition to changes with ion complexation, making the solvent environment in which the hydrogel is located visualized and detectable. In mixed solvents of water and dimethyl sulfoxide in different proportions, the maximum emission peak position of the metal complex hydrogel shifts from 485nm to 503nm, and the color gradually changes from blue to green.
[0113] In summary, the present invention uses a solvent exchange method to introduce hydrophobic monomers into the hydrogel system to construct a high-strength and anti-swelling hydrogel with adjustable mechanical and fluorescent properties, so that the hydrogel mechanical properties are improved while giving it fluorescent properties, and it can be applied to underwater environments. The ion and solvent responsiveness derived from the ion complexation and hydrophobic association mechanism makes the hydrogel have adjustable mechanical and fluorescent properties, anti-swelling properties and excellent mechanical properties, and realizes the correlation between solvent responsiveness and fluorescent properties. Based on its performance, the hydrogel can be used in solvent detectors to monitor whether a solvent that is a good solvent for hydrophobic monomers has leaked in the water. It can also be used in shape memory materials, and the recyclable dual shape memory performance makes it more flexible. It has application value in the fields of optical flexible devices, shape memory materials and underwater sensors.
[0114] The implementation modes of the present invention are not limited thereto, and any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the invention.
Claims
1. Anti-swelling high-strength hydrogel with adjustable mechanical and fluorescence properties, characterized in that: The organic gel is obtained by soaking the organic gel in deionized water for 2 to 3 days to perform solvent exchange and then soaking the organic gel in a metal ion solution for 6 to 12 hours; the organic gel is composed of ( Z )-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide, methacrylic acid, n-butyl acrylate, and polyethylene glycol diacrylate are uniformly mixed in a third organic solvent, nitrogen is charged, an initiator is added, and polymerization is performed at 65-75° C. for 4-10 h to obtain; ( Z )-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide is prepared from ( Z )-4-amino-N'-(quinoline-2-methylene)phenylhydrazine and triethylamine are dissolved in a second organic solvent, stirred evenly, and then methacryloyl chloride is added dropwise, reacted under a nitrogen atmosphere, and purified to obtain; ( Z )-4-amino-N'-(quinoline-2-methylene)phenylhydrazine is prepared by adding p-aminobenzoylhydrazide and quinoline-2-carboxaldehyde to a first organic solvent, dropping glacial acetic acid, stirring and reacting at 80-90°C under nitrogen protection, and then purifying; the metal ion solution is Zn 2+ Solution; ( Z The molar ratio of )-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide, methacrylic acid and n-butyl acrylate is 1:(50~114):(6~30), and the molar concentration of polyethylene glycol diacrylate is 0.1~1% of the total molar concentration of methacrylic acid and n-butyl acrylate.
2. The method for preparing the anti-swelling high-toughness hydrogel with adjustable mechanical and fluorescent properties as claimed in claim 1, characterized in that The steps include: 1) Add p-aminobenzoyl hydrazide and quinoline-2-carboxaldehyde to the first organic solvent, add catalyst glacial acetic acid dropwise, and stir at 80-90°C for 24-48h under nitrogen protection; after the reaction, filter to obtain a crude product, wash, and dry to obtain ( Z )-4-amino-N'-(quinoline-2-methylene)phenylhydrazine; 2) Z )-4-amino-N'-(quinoline-2-methylene)phenylhydrazine and triethylamine are dissolved in a second organic solvent, stirred evenly, and then methacryloyl chloride is added dropwise, and the mixture is reacted at 50-70°C for 12-24 h under a nitrogen atmosphere; after the reaction, the mixture is precipitated, filtered to obtain a crude product, and then recrystallized and dried to obtain ( Z )-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide; 3) Z )-N-(4-(2-(quinoline-2-methylene)hydrazine-1-carbonyl)phenyl)methacrylamide, methacrylic acid, n-butyl acrylate, and polyethylene glycol diacrylate are uniformly mixed in a third organic solvent, nitrogen is charged, an initiator is added, and polymerization is carried out at 65-75° C. for 4-10 h to obtain an organic gel; 4) Soak the organogel in deionized water at room temperature for 2 to 3 days for solvent exchange, changing the water every 12 to 24 hours to obtain a hydrogel; 5) The hydrogel was immersed in a metal ion solution at room temperature for 6 to 12 h to obtain a swelling-resistant, high-strength and tough hydrogel with adjustable mechanical and fluorescence properties.
3. The method for preparing the anti-swelling high-toughness hydrogel with adjustable mechanical and fluorescence properties according to claim 2, characterized in that: In step 1), the molar ratio of p-aminobenzoic acid hydrazide to quinoline-2-carboxaldehyde is 1:1, and the amount of glacial acetic acid added per millimole of p-aminobenzoic acid hydrazide is 0.02-0.04 ml.
4. The method for preparing the anti-swelling high-toughness hydrogel with adjustable mechanical and fluorescence properties according to claim 2, characterized in that: In step 2), the ( Z The molar ratio of )-4-amino-N'-(quinoline-2-methylene)phenylhydrazine to methacryloyl chloride is 1:1.1-1:1.6, and the molar ratio of methacryloyl chloride to triethylamine is 1:1.1-1:1.
2.
5. The method for preparing the anti-swelling high-toughness hydrogel with adjustable mechanical and fluorescence properties according to claim 2, characterized in that: In step 3), the total molar concentration of methacrylic acid and n-butyl acrylate in the third organic solvent is 3-6 M, and the amount of the initiator used is 1-3% of the total mass of methacrylic acid and n-butyl acrylate.
6. The method for preparing the anti-swelling high-toughness hydrogel with adjustable mechanical and fluorescence properties according to claim 5, characterized in that: In step 3), the relative molecular mass of the polyethylene glycol diacrylate is one or more of 400, 600 and 1000; and the initiator is azobisisobutyronitrile, potassium persulfate or ammonium persulfate.
7. The method for preparing the anti-swelling high-toughness hydrogel with adjustable mechanical and fluorescence properties according to claim 2, characterized in that: In step 1), the first organic solvent is one or more of acetonitrile, methanol and dimethyl sulfoxide; in step 2), the second organic solvent is N-methylpyrrolidone; in step 3), the third organic solvent is one or more of acetone and dimethyl sulfoxide.
8. The method for preparing the anti-swelling high-toughness hydrogel with adjustable mechanical and fluorescence properties according to claim 2, characterized in that: In step 1), the washing is performed with isopropanol; in step 2), the precipitation is performed in water, and the recrystallization is performed by dissolving the crude product in pyridine and then recrystallizing it in n-hexane or ether; in step 4), each gram of the organogel is immersed in 100-200 ml of deionized water.
9. The method for preparing the anti-swelling high-toughness hydrogel with adjustable mechanical and fluorescence properties according to claim 2, characterized in that: In step 5), the Zn 2+ The solution was prepared by dissolving zinc acetate dihydrate in deionized water; 4 to 8 ml of 0.001 to 0.3 M metal ion solution was added per gram of hydrogel.
10. Use of the anti-swelling high-toughness hydrogel with adjustable mechanical and fluorescent properties as claimed in claim 1 in solvent detection, wherein the solvent is a mixed solvent of dimethyl sulfoxide and water in different proportions.
